Empowering Education: A Comprehensive Review of IoT-Integrated Smart Education System (International Journal of Food and Nutritional Sciences, 2022)
The Smart Education System leverages advanced IT technology, particularly Internet of Things (IoT) and cloud computing, to enhance various components of the educational system. The integration of intelligent technologies in the education sector is becoming increasingly vital, and IoT plays a crucial role in Information and Communication Technology (ICT) and social development. The continuous growth of connected devices in education allows for a wealth of data, enabling campus leaders to engage in iterative processes with students, teachers, administrators, and service providers, transitioning from a transactional relationship to a more dynamic and responsive educational environment. The emphasis on creating a person-centered environment within smart campuses aligns with the broader strategy of smart environments. This strategy aims to enhance productivity, promote sustainability, and improve the everyday conditions of educational institutions' constituents. The research, based on an analysis of literature from various papers published in journals and online sources, aims to elucidate the role of IoT in the development of the Smart Education System. However, it acknowledges a limitation in that it focuses solely on the application components of the subject matter, omitting physical components. Conventional educational delivery and management methods may fall short in meeting the demands of this industrial era. Therefore, disruptive technologies like IoT hold significant potential for transforming the current educational setup. The research work provides an overview of IoT applications in educational settings, examining the perspectives of school management, teachers, and learners. The paper delves into recent research to showcase how IoT benefits school managers, teachers, and learners. It explores the three perspectives mentioned earlier, shedding light on the practical applications of IoT in the educational landscape. Additionally, the research identifies bottlenecks in IoT applications, elucidating security, privacy, scalability, reliability, and dehumanization as key constraints in implementing IoT technologies within educational settings. The comprehensive overview aims to contribute to the understanding of the role and challenges of IoT in the evolving field of smart education.